Dealing with Negative Observations While Calculating Inequalities – Examining Asset Declarations of Polish Deputies - Rychlicki, Paweł; Kozaczewska, Kornelia; Jastrzębski, Filip (Radzenie sobie z obserwacjami ujemnymi przy obliczaniu nierówności – badanie oświadczeń majątkowych polskich posłów, 2023)
Researchers and statisticians often face challenges when it comes to measuring inequalities of income, expenditure, and wealth. The aim of this paper was to draw attention to the problem of negative inputs, which are often ignored or treated as errors when measuring poverty and inequality. The paper presents the current state of proposals for normalising the Gini index in the presence of negative inputs, followed by a thorough data analysis of Polish parliamentary deputies’ asset declarations for the year 2021. After a theoretical comparison of different Gini index normalisation methods, empirical results showed that even with a relatively small amount of negative values, differences between the normalisation methods are significant and need to be addressed. Two methods of decomposition of the Gini index are also shown to assess how inequality manifests itself between the political parties and how different inputs impact on the overall inequality. Hence, these decompositions show the influence of debts and liabilities on the Gini index.
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2022-2023, Nr 20-21 (26-27), s. 31-46
Keywords: Gini index; inequalities; debt; negative values; indeks Giniego; nierówność; dług; wartości ujemne